Scrum XPerience: A New Approach for Agile Teaching - Aragão, Paulo André Pimenta; Souza, Rogéria Cristiane Gratão (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
Agile methodologies stand out in the software development processes by predicting changes and promoting better communication among team members, with Scrum and eXtreme Programming being the most used. So, training future software professionals in such methodologies becomes indispensable. Given that educational games make the teaching-learning process more dynamic and efficient, this article analyzed the existing solutions to verify deficiencies to be overcome. Thus, this paper resulted in the presentation of an educational game prototype, called Scrum XPerience, capable of contributing to the evolutionary development of future educational games, more complete concerning current solutions, aimed at teaching agile methods. Undergraduate and graduate students and professors from the Computing area evaluated the prototype. The results attest that Scrum XPerience is a potential proposal for teaching agile methodologies, correcting existing deficiencies in current solutions, and fostering the evolution of research in this area. In addition, it was possible to identify opportunities for future improvements to upgrade Scrum XPerience and, consequently, the development of future educational games aimed at agile teaching, increasing the quality of training of the students on this topic.